Image-Guided Spinal Surgery and Robotics in MIS: Where Are We Now? - Chiung Chyi Shen (Indoscholar, 2018)
Use of pedicle screws is widespread in spinal surgery for degenerative, traumatic, and oncological diseases. The conventional technique is based on the recognition of anatomic landmarks, preparation and palpation of cortices of the pedicle under control of an intraoperative C-arm (iC-arm) fluoroscopy. With these conventional methods, the median pedicle screw accuracy ranges from 86.7% to 93.8%, even if perforation rates range from 21.1% to 39.8%. The development of novel intraoperative navigational techniques, commonly referred to as image-guided surgery (IGS), provide simultaneous and multiplanar views of spinal anatomy. IGS technology can increase the accuracy of spinal instrumentation procedures and improve patient safety. These systems, such as fluoroscopy-based image guidance (